Electromagnet and switchboard for slewing crane - Pedrosa, Delfim Duarte Rolo (2006)
This paper presents an electromagnet and a switchboard used on a science fair slewing crane described in a separate paper. The electromagnet can lift 50kg loads. The switchboard includes a transformer that powers the electromagnet. It also contains relays, contactors and inverters that allow the operation of the crane three-phase motors using a single-phase power supply. Crane slewing is limited to an 180º angle, for safety reasons. Pressing an emergency button switches off all command circuits. An 8051 microcontroller-based system determines the vertical position of the electromagnet, which cannot be switched off while being on a high position, not even if the emergency button is pressed.